Optimalisasi Digital Marketing Berbasis TikTok Sebagai Upaya Meningkatkan Penjualan UKM 3D Printing - Prabaswari, Atyanti Dyah; Santoso, Dwi Wahyu; Sutrisno, Wahyudhi; Purnomo, Hari; Cahyo, Winda Nur; Saputri, Afiana (Universitas Islam Indonesia, 2026)
This community service activity focuses on optimizing the integration of Digital Marketing to increase sales in a 3D Printing SME through the utilization of the TikTok platform. The problems faced by the partner include suboptimal use of digital media, unintegrated marketing strategies, and low promotional effectiveness. The purpose of this activity is to assist the SME in developing a more effective, measurable, and consumer-oriented Digital Marketing strategy in the digital era. The method used is a qualitative descriptive approach with the application of design thinking, which consists of five stages: empathize, define, ideate, prototype, and test. The implementation of this activity includes several steps such as introducing TikTok-based Digital Marketing, content creation training, branding assistance, integration with marketplaces, and evaluation of the implemented strategies. This approach enables the development of innovative solutions that align with the needs of the partner. The results show improvements in several indicators, Shopee followers increased from 170 to 321, the Shopee customer rating improved from 4.8 to 4.9 with the number of reviews rising from 1,100 to 2,000, and the average TikTok content reach achieved 256 views per content, and increased sales volume. Therefore, it can be concluded that the integration of Digital Marketing through TikTok effectively enhances promotional performance, expands market reach, and contributes to sustainable sales growth for the 3D Printing SME.